Kaestlea: A new genus of scincid lizards (Scincidae: Lygosominae) from the Western Ghats, south-western India - Eremchenko, Valery K.; Das, I. (Centre for Herpetology, Madras Crocodile Bank Trust, 2004)
A lineage of lygosomines, allocated in the past variously to Scincella, Lygosoma, Leiolopisma and Asymblepharus, comprising five nominal species endemic to the Western Ghats of south-western India, is allocated to a new genus, Kaestlea.The genus includes the following species: Mocoa bilineata Gray, 1846; Mocoa travancorica Beddome, 1870; Lygosoma beddomii Boulenger, 1887; Lygosoma laterimaculatum Boulenger, 1887 and Lygosoma (Leiolopisma) travancoricum var. palnica Boettger, 1892. Lectotypes of all recognised species are designated. The relationships of these species with others lygosomine skinks of Asia and America (including the genera Scincella, Sphenomorphus and Asymblepharus) are discussed. Diagnoses and a key to the species of Kaestlea are provided.